Pembelajaran Kontekstual Tipe Hands On Activity Dan SAVI (Somatic, Auditory, Visual And Intelectual) Untuk Meningkatkan Kemampuan Pemahaman Matematis Siswa SMP - Rosmaria Sihotang; Sonya Tauran (LPPM Universitas Advent Indonesia, 2020)
The purpose of this study is to improve the mathematical understanding ability of junior high school students through the application of contextual learning model type Hands-on Activity (HOA) and SAVI learning (Somatic, Auditory, Visual, and Intelectual). The design of this study uses a comparative casual. The research sample consisted of 55 VIII grade students of SMPN 10 Cimahi, West Java. The research instruments used were test and non-test instruments. The test instrument consisted of mathematical understanding questions about the construction of the plan figures, and the non-test was in the form of a questionnaire of students' responses to the learning strategy. Hypothesis testing used was the t-test at a significant level (α = 0.05). The results of the study show that: are 1) The students' mathematical understanding ability has increased in the moderate category, 2) There is a difference in increasing mathematical understanding ability between students who obtain the contextual learning model type Hands-on Activity (HOA) and students who obtain the SAVI model (Somatic, Auditory, Visual, and Intellectual, 3) Students respond favorably to the contextual type of Hands-on Activity (HOA) learning model and the SAVI learning model.